2020
DOI: 10.3389/fonc.2020.00086
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Systematic Lymphadenectomy in Patients With Optimally Debulked Advanced Ovarian Cancer: A Meta-Analysis

Abstract: Background: The effect of systematic lymphadenectomy (SL) on survival in patients with optimally debulked advanced ovarian cancer remains unclear. We evaluated the therapeutic value of SL in advanced ovarian cancer patients who underwent primary optimal debulking surgery. Methods: A meta-analysis was carried out using articles retrieved from the PubMed, Embase, and Cochrane databases. Overall survival (OS) and progression-free survival (PFS) were compared between patients who underwent SL and those who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Results were similar in two other meta-analyses [ 35 , 36 ]. Latest meta-analysis showed greater overall survival, but not PFS, in patients with optimally debulked advanced ovarian cancer [ 37 ]. Nevertheless, these results must be cautiously interpreted due to the few included randomized trials, which were against systematic LND [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results were similar in two other meta-analyses [ 35 , 36 ]. Latest meta-analysis showed greater overall survival, but not PFS, in patients with optimally debulked advanced ovarian cancer [ 37 ]. Nevertheless, these results must be cautiously interpreted due to the few included randomized trials, which were against systematic LND [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…While lymphadenectomy led to a significant improvement in OS [hazard ratio (HR) = 0.64; 95% confidence interval (CI): 0.49-0.84, p < 0.01], this effect was not seen in PFS (HR = 0.89, 95% CI: 0.69-1.15, p = 0.38). In the subgroup analysis, it was reported that it did not affect the PFS (HR = 1.09, 95% CI: 0.91-1.30, p = 0.33) and OS (HR = 0.81, 95% CI: 0.66-1.00, p = 0.05) [24]. In the uni-variate analysis in our study, although the mortality risk decreased in patients who had undergone SLND, there was no statistically significant difference (HR = 0.89; 95% CI: 0.65-1.22, p = 0.480).…”
Section: Discussionmentioning
confidence: 96%
“…They showed that patients who underwent systematic lymphadenectomy had a marginally significantly improved PFS (p = 0.059) and significantly improved OS (p < 0.001) compared with those who underwent lymph node sampling. In the meta-analysis of 2425 patients with ovarian cancer, Wang et al [25] reported significantly improved OS (Hazard ratios (HR): 0.64, 95% Confidence interval (CI): 0.49-0.84, p < 0.01) but not PFS (HR: 0.89, 95% CI: 0.69-1.15, p = 0.38) in patients who underwent systematic lymphadenectomy compared to those without systematic lymphadenectomy.…”
Section: Pelvic and Paraaortic Lymphadenectomymentioning
confidence: 99%